Vacuum dried and rehydratable product from grated coconut meat (Cocos Nucifera Linn.) - Barbudo, Ma Carmencita Eulalia
The research study was conducted to develop a vacuum-dried grated coconut which can be rehydrated to resemble the fresh grated coconut commonly used in the country. The study was divided into two phases. In the first phase, the drying characteristic in terms of the drying curve was obtained by plotting the moisture content of the samples against time. The second phase was divided into two subphases, the first involving rehydration test and the second involves the sensory evaluation of the samples rehydrated in the first subphase. By process of elimination the temperature ranges utilized in the first phase was narrowed down to four since the first range of 40-50°C proved to be highly impractical because drying takes much longer. In Phase II, the temperature was established at 55°C for 15 minutes since heating at 65°C for 15 minutes made products desirability lower. Sensory evaluation results revealed that product sample 673 or dried at 60-70°C was preferred and at 5% level of significance, showed that the coconut milk obtained from the rehydrated sample are significantly different from each other. Statistical analysis showed that products 673, 961 and 722 have similarities and that product 673, 842, and 961 have similarities at 5% level of significan